On the Embryonic Development of the Nasal Turbinals and Their Homology in Bats - Ito, Kai; Tu, Vuong Tan; Eiting, Thomas P.; Nojiri, Taro; Koyabu, Daisuke (Frontiers in Cell and Developmental Biology, 2021)
Multiple corrugated cartilaginous structures are formed within the mammalian nasal capsule, eventually developing into turbinals. Due to its complex and derived morphology, the homologies of the bat nasal turbinals have been highly disputed and uncertain. Tracing prenatal development has been proven to provide a means to resolve homological problems. To elucidate bat turbinate homology, we conducted the most comprehensive study to date on prenatal development of the nasal capsule. Using iodine-based contrast-enhanced computed tomography (diceCT), we studied in detail the three-dimensional prenatal development of various bat species and non-bat laurasiatherians. We found that the structure previously identified as “maxilloturbinal” is not the true maxilloturbinal and is only part of the ethmoturbinal I pars anterior. Our results also allowed us to trace the evolutionary history of the nasal turbinals in bats. The turbinate structures are overall comparable between laurasiatherians and pteropodids, suggesting that pteropodids retain the ancestral laurasiatherian condition. The absence of the ethmoturbinal I pars posterior in yangochiropterans and rhinolophoids has possibly occurred independently by convergent evolution.